Effects of lactoferrin and lactoperoxidase‐containing food on the oral microbiota of older individuals. (12th October 2017) - Nakano, Manabu; Wakabayashi, Hiroyuki; Sugahara, Hirosuke; Odamaki, Toshitaka; Yamauchi, Koji; Abe, Fumiaki; Xiao, Jin‐Zhong; Murakami, Kohji; Ishikawa, Kentaro; Hironaka, Shouji
ABSTRACT: The oral microbiota influences health and disease states. Some gram‐negative anaerobic bacteria play important roles in tissue destruction associated with periodontal disease. Lactoferrin (LF) and lactoperoxidase (LPO) are antimicrobial proteins found in saliva; however, their influence on the whole oral microbiota currently remains unknown. In this randomized, double‐blinded, placebo‐controlled study, the effects of long‐term ingestion of LF and LPO‐containing tablets on the microbiota of supragingival plaque and tongue coating were assessed. Forty‐six older individuals ingested placebo or test tablets after every meal for 8 weeks. The relative abundance of bacterial species was assessed by 16S rRNA gene high‐throughput sequencing. Most of the bacterial species in supragingival plaque and tongue coating that exhibited significant decreases in the test group were gram‐negative bacteria, including periodontal pathogens. Decreases in the total relative abundance of gram‐negative organisms in supragingival plaque and tongue coating correlated with improvements in assessed variables related to oral health, such as oral malodor and plaque accumulation. Furthermore, there was significantly less microbiota diversity in supragingival plaque at 8 weeks in the test group than in the placebo group and low microbiota diversity correlated with improvements in assessed variables related to oral health. These results suggest that LF and LPO‐containing tablets promote a shift from a highly diverse and gram‐negative‐dominated to a gram‐positive‐dominated community in the microbiota of supragingival plaque and tongue coating. This microbial shift may contribute to improvements in oral health, including oral malodor and state of the gingiva.